Ferroelectric phase transition in lead germanate Pb₅Ge₃O₁₁ studied by ESR of Gd³⁺ probe - Trubitsyn, M.P.; Volnianskii, M.D.; Ermakov, A.S.; Linnik, V.G. (Condensed Matter Physics, 1999)
ESR spectra of Gd³⁺ probe have been studied in the range of ferroelectric phase transition TC=451 K in lead germanate Pb₅Ge₃O₁₁. Measurements of ESR line position have shown that local order parameter behaves in accordance with the mean ﬁeld theory approach in a broad (∼150 K) temperature interval below TC. Anomalous line width broadening observed around TC can be associated with a quasi-elastic central peak component of excitation spectrum, observed earlier using a light scattering experiment and attributed to static symmetry-breaking defects. ЕПР спектри iонiв Gd³⁺ вивчалися в iнтервалi сегнетоелектричного фазового переходу Tc=451 К кристалiв германату свинцю Pb₅Ge₃O₁₁. На пiдставi вимiрювання температурних залежностей положення ЕПР лiнiй показано, що поведiнка локального параметра порядку в досить широкому iнтервалi (∼ 150 К) сегнетоелектричної фази погоджується з теорiєю середнього молекулярного поля. Аномальне розширення резонансних лiнiй, що спостерiгається навколо Tc, може бути зiставлене з вузьким квазi-пружним центральним пiком у спектрах комбiнацiйного розсiяння свiтла i пов’язане зi статичними дефектами кристалічної гратки.